Nesting of Northern Bobwhites on Rangeland Versus Conservation Reserve Program Habitats in the Rolling Plains of Texas - Dale Rollins; Barrett A. Koennecke (National Quail Symposium Proceedings, 2017)
Conservation Reserve Program (CRP) contracts account for about 1.7 million ha in Texas, and are often touted as habitat for upland game birds. We compared nest site locations, hatch rates, and arthropod abundance for northern bobwhites (Colinus virginianus) on CRP versus rangeland habitats at the Rolling Plains Quail Research Ranch (RPQRR), Fisher County, Texas from 2008 to 2011. Nest sites were monitored via radio-marked females. Simulated nests (n 1⁄4 144/yr) were used to evaluate hatch rates between the 2 habitat types. Arthropod abundance (as an indicator of brood habitat) was measured annually in August using sweep nets and pitfall traps. We documented 103 nest sites, 14% were in CRP while the remaining 86% were in rangeland; bobwhites neither selected nor avoided CRP as nesting habitat. ‘Survival’ of simulated nests (i.e., percent intact at 28 days exposure) across the 4 years averaged 63.2% for CRP and 74.4% on rangelands. Arthropod availability was greater in rangeland in 3 of the 4 years studied. CRP pastures dominated by kleingrass (Panicum coloratum) were used for nesting in proportion to their availability, but rangeland provided better brood habitat.
Keywords: Bothriochloa saccharoides; Colinus virginianus; Conservation Reserve Program; introduced grasses; kleingrass; nesting; northern bobwhite; Panicum coloratum; Rolling Plains; Texas